Manajemen Strategi : Kajian Teori Resource Based View - Rima Elya Dasuki (Coopetition : Jurnal Ilmiah Manajemen, 2021)
This paper aims to analyze the framework of the Resource-Based View theory put forward by experts in strategic management, as well as to describe the SWOT framework, especially those related to strengths and weaknesses by identifying what are the strengths and capabilities of the company and avoiding weaknesses for competitive advantage. and is expected to be able to describe the concept of Resource-Based View and analyze the development of Resource-Based View theory in strategic management, and analyze the internal environment from the point of view of strengths and weaknesses that will help the company to be able to take advantage of existing opportunities and be able to avoid possible threats. arise, and analyze the company's capabilities that will affect the final product which includes dynamic skills, capacities, and resources. The research method used is based on a historical approach and literature review from the opinions of experts who discuss the theory of Resource-Based Value, both physical and non-physical in relation to capabilities and competencies in creating superior competitiveness, with the main study based on the opinion of strategic management experts. Mahoney Joseph T, J. Rajendran Pandian, 1992. This paper will be directed to the analysis of various opinions of economists regarding the resource framework that will produce a capability, namely the skills that exist in each individual. competitive of a company